Between Tolerant Containment and Concerted Constraint: Managing Madness for the City and the Privileged Family - Gong, Neil (American Sociological Review, 2019)
How do public safety net and elite private mental health providers cope with a key dilemma since psychiatric deinstitutionalization—managing madness when people have the right to refuse care? I observed two approaches to voluntary community-based services, one that tolerates “non-compliance” and deviant choices, and another that attempts to therapeutically discipline clientele. The puzzle, given theories of the paternalistic governance of poverty, is that select poor patients are given autonomy while the privileged are micro-managed. Drawing on comparative fieldwork in Los Angeles, I show how contrasting ecological pressures and resource bases shape divergent practices. In the context of urban poverty governance, mental health care and low-barrier housing offer a way to remove problem people from public space. This “tolerant containment” is linked to limited therapeutic capacity and the construction of clients as beyond transformation. In the context of family systems governance, elite private mental health care is a project to reform wayward relatives and equip them with respectable futures. A “concerted constraint” of deviance, akin to Lareau’s theory of privileged childrearing, is reserved for those who can afford rehabilitation and conceivably recover. Using these cases, I contribute to theories of social control and inequality in advanced liberal societies.